Transcriptome analysis of self- and cross-pollinated pistils revealing candidate unigenes of self-incompatibility in Camellia oleifera. Issue 1 (2nd January 2020) - He, Yifan; Song, Qianqian; Chen, Shipin; Wu, Yuefeng; Zheng, Guohua; Feng, Jinling; Yang, Zhijian; Lin, Wenjun; Li, Yu; Chen, Hui
ABSTRACT: Self-incompatibility (SI) is a mechanism used to prevent inbreeding and promote outcrossing in a wide variety of angiosperms. Camellia oleifera (Theaceae), is one of the most prominent wood oil plants. However, self-incompatibility results in a relatively low ratio of fruit/seed sets to flowers in C. oleifera . In this study, fluorescence microscopy and confocal microscopy were used to observe how pollen tube growth differed between cross- vs. self-pollination events. We found that self-pollen tubes appear twisted and clustered when growing to the base of the style and it is impossible for self-pollen tubes to reach the embryo sac to complete double fertilization. In contrast, pollen tubes from crossing events grow normally and reach the ovary to complete fertilization. We characterised candidate genes related to SI and investigated the underlying mechanisms regulating fertilization by performing RNA-seq on C. oleifera . In addition, we also conducted qRT-PCR on 20 unigenes to validate our RNA-seq data. We identified genes encoding protein kinases and phosphatases, Ca 2+ signaling proteins, transcription factors, CYP family members, and defense-related proteins as candidate genes related to SI in C. oleifera . With these genes identified, more thorough studies of SI mechanisms in C. oleifera have become possible.